Relações de gênero entre docentes dos Programas de Pós-Graduação da Universidade Tecnológica Federal do Paraná (UTFPR) e da Universidade Tecnológica de Compiègne (UTC-França): um estudo comparativo das carreiras de homens e mulheres - Kovaleski, Nadia Veronique Jourda (2013)
Currently, western universities are where research is mostly carried out. If western history shows some women getting into those temples of knowledge, today, they account for a considerable number of faculty members/researchers. A revision of literature revealed that women and men do not have the same job opportunities when it comes to the career as a faculty member/researcher. Therefore, a comparative analysis of gender relations in the graduate programs at the Federal University of Technology of the State of Paraná (UTFPR) and the University of Technology of Compiègne - France (UTC) was seen as relevant. The aim of the research was twofold: to find out whether women from these universities of technology faced discriminatory practices or, instead, a greater acceptance and to investigate the existence of the famous “glass ceiling” that limits women`s job promotion. The research was qualitative with content analysis and was characterized as comparative. The data collection was conducted with a semi-structured interview with 16 faculty members/researchers from the UTFPR and 17 faculty members/researchers from the UTC. The findings and conclusion of this research are that the career as a faculty member/researcher calls for a great sacrifice and it is more socially adapted to men than women for two main reasons: first, a bigger investment on the part of women than men concerning reproductive work, and second, the existence of mechanisms of discrimination practices in the professional university career that hinder women`s professional advancement.